THE RELATIONSHIP BETWEEN INFLATION, POPULATION, ARABLE LAND AND AGRICULTURAL PERFORMANCE IN MALAYSIA - WEE, POK HSIEN (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The main purpose of this study is to investigate the relationship between the inflation, population, arable land and agricultural productivity in Malaysia from the period of 1963 until 2012. The variables that included in this study are inflation rate, percentage of population with age group of 15-64 years, arable land in hectares, and value added in agriculture sector in current USD. The resource of data is solely extracted from World Bank. The used research methodologies are Augment Dickey-Fuller (ADF), Phillip-Perron (PP), and Kwiatkowski, Phillip, Schmidt and Shin (KPSS) unit root tests, Johansen and Juselius cointegration test, and Vector Error Correction Model (VECM) Granger causality test. The findings of this study identified that there is one cointegrating vector in the estimated model and inflation rate is the most endogenous variable in both short run and long run relationship while agricultural productivity is the most exogenous variable in the short run relationship.